Islam and development in Asia - Shukri, Muhammad Aziz; Kosugi, Yusushi; Loqman, Muhammad; Endo, Shigeru; Muhammady, Muhammad 'Uthman el-; Abdul-Majeed, Abu-Bakar; Salleh, Shaikh Mohd Saifuddeen Shaikh Mohd Salleh (IKIM, 1998)
Ibrahim, Ismail bin Haji: Introduction - Islam in Southeast Asia. - S. 1-4. Loqman, Muhammad: Islamic banking and business. Laws vis-a-vis economic development. - S. 9-49. Endo, Shigeru: Non-interest financing and the Islamic economies. - S. 51-56. Muhammady, Muhammad 'Uthman El-: The Muslim society as an information society. - S. 61-65. Abdul Majeed, Abu Bakar: Information age. An Islamic perspective. - S. 67-84. Kosugi, Yusushi: OIC as an international Shura body of the Islamic world. - S. 89-95. Shukri, Muhammad Aziz: War and peace in Islam. - S. 97-104. Resolutions. - S. 105-115